2021
DOI: 10.7163/gpol.0201
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of human bioclimate of Vranje health resort (Serbia) based on Universal Thermal Climate Index (UTCI) with the focus on extreme biothermal conditions

Abstract: The study deals with an assessment and interpretation of the bioclimatic conditions in Vranje (southern Serbia). The study aims at temporal distributions of bioclimatic conditions focussing on extreme thermal stress based on the Universal Thermal Climate Index (UTCI). The meteorological data required for the calculation of UTCI concern hourly (7 and 14 CET) weather data collected for the period 2000-2017. The frequency of very strong heat stress (VSHS), very strong cold stress (VSCS) and extreme cold stress (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Well-visited tourist places in Serbia are also spas, however, according to Stevnović's (2019) analysis of the equivalent temperatures of the Vranjska spa, during the two summer months, July and August, the "overheated" weather type occurs, represented by the "little humidity" class (50-58°C), which from the aspect of tourism it is not favorable because this class also occurs in the cities that represent the emitting areas of the largest number of tourists. Also, an analysis of the Universal Thermal Index of the Vranjski region, to which the Vranjska spa belongs, for the period from 2000 to 2017 found that during July, August and September the class of "strong moderate stress" occurs, which is not the case in Zlatibor (Pecelj, Błażejczyk , Vagic, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-visited tourist places in Serbia are also spas, however, according to Stevnović's (2019) analysis of the equivalent temperatures of the Vranjska spa, during the two summer months, July and August, the "overheated" weather type occurs, represented by the "little humidity" class (50-58°C), which from the aspect of tourism it is not favorable because this class also occurs in the cities that represent the emitting areas of the largest number of tourists. Also, an analysis of the Universal Thermal Index of the Vranjski region, to which the Vranjska spa belongs, for the period from 2000 to 2017 found that during July, August and September the class of "strong moderate stress" occurs, which is not the case in Zlatibor (Pecelj, Błażejczyk , Vagic, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…based on their values it calculates bioclimatic indices used to determine the bioclimatic characteristics of the studied area (Stanković, 1995;Unkašević, 2003;Pecelj, Milinčić, Pecelj, 2007;Stojićević, 2016). Numerous authors have analyzed the various bioclimatic indices of urban centers (Pecelj et al, 2020;Bursać Martić, Stričević, Gocić, 2021;Lukić et al, 2019;Milentijević et al, 2018), spa (Pecelj, Błażejczyk, Vagic, 2021;Stevanović, 2019;Stojićević, Basarin, Lukić, 2016;Maćejka, 2003), mountains (Pecelj et al, 2017;Basarin et al, 2018;Vujević, 1961) but also regional units of Serbia (Basarin et al, 2017;Stojićević, 2016;Malinović Milićević, 2013) and certain places in its surrounding (Šušnjar, Pecelj, 2014;Trbić, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A change in the frequency of extreme biothermal conditions in recent years has been observed in Serbia by Pecelj et al (2021), and in Poland by krzyżewska et al (2021). kuchcik et al (2021) recognised increase in maximum UTCI values in summer in the north-east, north-west and south of Poland, as well as in UTCI minimum values in the entirety of Poland in the period 1951-2018.…”
Section: Introductionmentioning
confidence: 93%
“…In recent years urban OTC, the application of UTCI, and other thermal indices have become the subjects of many scientific studies by numerous researchers from Serbia and other Western Balkan countries [21,22,25,[46][47][48][49][50][51]. Regarding the application of UTCI in studies of Serbian urban bioclimate, this index was analyzed, e.g., by Pecelj et al in order to compare bioclimatic conditions in the urban and suburban zones of Belgrade [52].…”
Section: Introductionmentioning
confidence: 99%